2021
DOI: 10.1111/scd.12583
|View full text |Cite
|
Sign up to set email alerts
|

Dental experiences of a group of autistic adults based in the United Kingdom

Abstract: Aims Previous international research has shown that autistic people have difficulty accessing dental care due to sensory processing, anxiety and communication issues. However, it is not known whether autistic adults in the United Kingdom are experiencing similar dental care barriers. The current study investigated autistic adults’ dental experiences in the United Kingdom. Methods and results A mixed methods survey was given to self‐selecting autistic (n = 37) and non‐autistic adults (n = 43) to compare whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(105 reference statements)
1
7
0
Order By: Relevance
“…The highest endorsed barriers to accessing health care services were related to sensory issues, behavioural challenges, and cost. These barriers are broadly consistent with other studies exploring specific barriers to oral health care in children and adults on the autism spectrum 11 , 12 , 27 , 28 . Uniquely, we reported that these barriers were more frequently endorsed for children with greater adaptive functioning difficulties and consequently more likely to have higher support needs.…”
Section: Discussionsupporting
confidence: 91%
“…The highest endorsed barriers to accessing health care services were related to sensory issues, behavioural challenges, and cost. These barriers are broadly consistent with other studies exploring specific barriers to oral health care in children and adults on the autism spectrum 11 , 12 , 27 , 28 . Uniquely, we reported that these barriers were more frequently endorsed for children with greater adaptive functioning difficulties and consequently more likely to have higher support needs.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, in a recent study of autistic people's dental experiences in the UK, autistic adults did not mention a need for caregivers to attend the appointment with them, as mentioned here, and autistic individuals expressed that their anxiety stemmed from known (mainly sensory) concerns rather than concerns about the unknown as dentists speculated in the current study. 26 Further, dentists in the current study recommended using strategies (like incentives) that autistic adults did not mention in the previous study. 26 These variations in opinion highlight the importance of including patient voice when seeking to understand and ameliorate challenges encountered.…”
Section: Discussionmentioning
confidence: 67%
“…26 Further, dentists in the current study recommended using strategies (like incentives) that autistic adults did not mention in the previous study. 26 These variations in opinion highlight the importance of including patient voice when seeking to understand and ameliorate challenges encountered. Some of these discrepancies, however, may be due to differences in approaches for autistic children versus autistic adults.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A study specifically examining the experience of dental services revealed that autistic adults without ID more often felt forced to proceed with dental treatment they were not prepared for and recalled more painful dental experiences than a neurotypical control group ( Blomqvist et al 2014 ). A UK online survey reported significantly more negative overall experiences and lower satisfaction scores associated with dental communication, sensory sensitivities, and knowing what was going to happen at a dental visit from autistic adults without ID ( McMillion et al 2021 ). Although higher dental anxiety levels were reported in both studies, neither study specifically investigated a relationship between previous child oral health experience and current reported anxiety or interaction with dental services.…”
Section: Introductionmentioning
confidence: 99%